The Effect Of Corporate Social Responsibility On Financial Performance In Telecommunication Companies Listed On The Indonesia Stock Exchange (Case Study On Telecommunication Companies Listed On The Indonesia Stock Exchange 2017-2021) - Sari, Putri Regita Permata; Sudarsono, Bambang (Eco-Entrepreneur, 2023)
This research was conducted to find out whether Corporate Social Responsibility (CSR) has a significant effect on financial performance (ROE, NPM, CR, DER) in telecommunications sector companies listed on the Indonesian stock exchange in 2017-2021. This type of research is quantitative. The sample of this research is secondary data obtained from the company's annual report and sustainability report. The data analysis technique used is financial ratio analysis and simple regression analysis with the help of the IMB 26 SPSS program. The results showed that Corporate Social Responsibility (CSR) had no significant effect on Return on equity (ROE), and Corporate Social Responsibility (CSR) had a significant negative effect on Net Profit Margin (NPM), Current Ratio (CR), Debt To Equity Ratio ( DER).